Exploring potential applications of measles and rubella microarray patches (MR-MAPs): use case identification - Malvolti, Stefano; Ko, Melissa; Menozzi-Arnaud, Marion; Mantel, Carsten; Jarrahian, Courtney; Amorij, Jean-Pierre; Giersing, Birgitte; Hasso-Agopsowicz, Mateusz (Frontiers in Public Health, 2023)
Innovative vaccine products will be critical in helping to address the existing implementation barriers that have prevented the achievement of the measles and rubella (MR) vaccine coverage targets. Overcoming those barriers will be necessary to achieve the “Immunization Agenda 2030” goals. Microarray patches (MAPs), an innovative needle-free delivery device currently in clinical development, can be a potential game changer in this respect and contribute to the equitable delivery of vaccines in low- and middle-income countries and contribute to pandemic preparedness and response. Developing in-depth knowledge of the most desired and impactful uses of MR-MAPs can prove critical to identify the critical attributes of the target product profile, inform policy and adoption decisions, and help to evaluate the potential public health and economic value of this technology. The first step in this process is the definition of the potential use cases for MR-MAPs, i.e., where and how this product is most likely to be used within the immunization programme. By applying a design-based user-centric approach, we implemented a three-step process, including a desk review, a survey and interviews, to define the most relevant use cases for MR MAPS. As a result, six use cases have been identified relevant across all different countries and immunization program designs and validated by experts. Those use cases have already informed the demand estimate for MR-MAPs and provided the foundation for developing an initial Full Vaccine Value Assessment. We trust that, in future, they will be very valuable in the future to ensure that the roll-out of this promising innovation is designed in a way that allows maximizing the impact, particularly in those populations and countries more in need.